Cognitive-behavioral factors associated with sleep quality in chronic pain patients. - Ashworth, P; Davidson, K; Espie, C (2010)
People with chronic pain commonly complain of sleep disturbance. This study reports the characteristics of the pain and sleep of a large sample of patients with chronic pain (n = 160). This study compared subgroups of good sleepers with pain (n = 48) and poor sleepers with pain (n = 108). Poor sleepers with pain were younger and reported more pain, pain-related disability, depression, pain-related anxiety, and dysfunctional beliefs about sleep. Using simultaneous regression analysis, this study examined the roles of pain, dysfunctional beliefs about sleep, pain-related disability, depression, and pain-related anxiety in predicting concurrent sleep quality. The findings are relevant to the development of models of sleep disturbance comorbid with chronic pain.